👤

If P(x)=x4-4x2 + 3x+2 then P(2)=____show complete solution


Sagot :

[tex] \large\underline \bold{{SOLUTION}}[/tex]

Substitute the value of x which 2 to the polynomial function

[tex]\longmapsto\rm{P(x)=x^4-4x^2-3x+2}[/tex]

[tex]\longmapsto\rm{P(2)=2^4-4(2)^2-3(2)+2}[/tex]

[tex]\longmapsto\rm{P(2)=16-4(4)-6+2}[/tex]

[tex]\longmapsto\rm{P(2)=\cancel{16-16}-6+2}[/tex]

[tex]\longmapsto\boxed{\rm{P(2)=-4}}[/tex]

[tex] \large\underline{ \bold{ANSWER}}[/tex]

  • [tex]\textsf{P(2) = -4}[/tex]